Diseño de morteros con los agregados finos de los 4 principales ríos de la provincia de El Oro - Paccha Ramírez, Neysor Bryan (My University, 2023)
The titling work presented below consists of making mortar designs using the fine aggregates of the main rivers in the lower part of the province of El Oro. The rivers that were chosen to analyze their aggregate are the following. Arenillas River, Santo Rosa River, Jubones River and the Pital River. As a first point to be able to design the mortars, the extractions of the samples of the fine aggregates were made. With the samples obtained we can carry out the corresponding tests to be able to know the characteristics that these possess, in such a way that whose characteristics serve us to carry out a correct design. The tests that were carried out on the samples were the following. dry volumetric weight, colorimetry, specific density, absorption, moisture content and granulometry. All these tests are essential to be able to determine the characteristics that these aggregates have and based on these characteristics to be able to design the mortar in an adequate way in such a way that it can be known if the design complies with the compressive strength of the Ecuadorian regulations. The dosage to be used for the design of the mortars will be 1:2. Using this dosage, the - ECUADORIAN TECHNICAL STANDARD NTE INEN 2 518:2010- indicates that the compressive strength of this mortar must be equal to or greater than 160 kg/cm2.
El trabajo de titulación que se presenta a continuación consiste en realizar diseños de morteros utilizando los agregados finos de los principales ríos de la parte baja de la provincia de El Oro. Los ríos que se escogieron para analizar su agregado son los siguientes. río Arenillas, río Santo Rosa, río Jubones y el río Pital. Como primer punto para poder diseñar los morteros se hizo las extracciones de las muestras de los agregados finos. Con las muestras obtenidas podemos llevar a cabo los ensayos correspondientes para poder saber las características que estos poseen, de tal manera que cuyas características nos sirvan para realizar un correcto diseño. Los ensayos que se realizaron a las muestras fueron los siguientes. Peso volumétrico seco, colorimetría, densidad específica, absorción, contenido de humedad y granulometría. Todos estos ensayos son esenciales para poder determinar las características que poseen estos agregados y con base en estas características poder diseñar de una forma adecuada el mortero, de tal manera que el diseño cumpla con la resistencia a compresión de la normativa ecuatoriana. La dosificación que se utilizará para el diseño de los morteros será de 1:2. Usando esta dosificación la - NORMA TÉCNICA ECUATORIANA NTE INEN 2 518:2010- nos indica que la resistencia a compresión de este mortero debe ser igual o mayor a 160 kg/cm2.
Keywords: ENSAYO; ESPECIFICACION; NORMA; AGREGADO